후단 공정을 고려한 공전해의 (Co-Electrolysis) 가능성과 향후 과제 - 오민준; 양성은 (The Korean Ceramic Society, 2024)
Global warming has intensified in recent years, necessitating abrupt changes in the chemical industry to dramatically reduce CO2 emissions. Electrochemical CO2 conversion is one of the most promising carbon capture and utilization technologies. High-temperature co-electrolysis using solid oxide electrolysis cells (SOECs) efficiently produces syngas (H2 and CO), a key feedstock for synthesizing hydrocarbons. Here, we review the opportunities and challenges of co-electrolysis technology, focusing on its integration with downstream processes. We introduce the basic principles of co-electrolysis, discuss operating conditions affecting syngas composition and carbon deposition, and explore direct methane production under high pressure operation. Various downstream processes utilizing syngas from co-electrolysis are examined, including the Fischer-Tropsch process for e-fuel, e-CO, e-methanol, and e-methane. Then, we summarize the current development status of SOEC and co-electrolysis technology, highlighting industrial efforts for commercialization. Finally, we discuss future prospects, emphasizing the need to improve system durability, enhance economic viability through integration with renewable energy, and develop low-temperature SOECs.